Sustainable tourism development : the case of Barbados - Greenidge, Kevin (Central Bank of Barbados [St. Michael]BB, 2007)
Examines the sustainability of tourism development in Barbados. Finds that tourism development in Barbados is on a sustainable path in harmony with the environment.